Infant nasal nitric oxide over time: natural evolution and impact of respiratory tract infection. Issue 6 (21st June 2018) - Marthin, June K.; Philipsen, Maria C.; Rosthoj, Susanne; Nielsen, Kim G.
Nasal nitric oxide (NO) discriminates between patients with primary ciliary dyskinesia (PCD) and healthy individuals. We report feasibility of measurement and natural evolution of nasal NO and upon the impact of respiratory tract infection (RTI) on nasal NO in healthy infants (HI), followed from birth until age 2 years, with comparison to nasal NO in infant PCD. Tidal-breathing nasal NO measurements were performed at scheduled visits at 2 weeks old and at 4, 8, 12, 18 and 24 months old, with extra visits during RTIs. Historical nasal NO measurements for infant PCD were included for comparison. Altogether, 224 nasal NO measurements were performed in 44 enrolled infants. Median newborn nasal NO was 46 ppb (interquartile range (IQR) 29–69 ppb), increasing at a rate of 5.4% per month up to 283 ppb (IQR 203–389 ppb) at the age of 2 years. RTIs in 27 out of 44 infants temporarily suppressed nasal NO by 79%. Values for nasal NO in seven infants with PCD ranged from 6–80 ppb. The success rate to accept nasal NO sampling was 223 out of 224 measurements (99.6%). Tidal-breathing nasal NO measurement was indeed feasible in infancy and nasal NO in HI increased significantly up to 2 years of age, in opposition to nasal NO in PCD cases, which stayed low past 2 years of age. RTI episodes caused marked, temporary reductions in nasal NO in HI indistinguishable from that in infant PCD, suggesting that nasal NO should be measured in RTI-free intervals. Nasal NO is feasible in infants, increases from 0–2 years and is suppressed to PCD levels by respiratory infections http://ow.ly/7AsR30jPMSf